Uterine rupture at the fundus during pregnancy: a case report - V., Venkatesh K.; B., Harsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Rupture of a gravid uterus is a surgical emergency. Predisposing factors include a scarred uterus. Spontaneous rupture of an unscarred uterus during pregnancy is a rare occurrence. We hereby present the case of a spontaneous complete uterine fundal rupture at Karnataka Institute of Medical Sciences, Hubli, Karnataka, India. The patient had a history of septal resection. Spontaneous uterine rupture occurs when there is an upper segment uterine scar. This case report shows that past history of septal resection is a risk factor for the presence of uterine scar.